مێژووى شیعر و ئەدەبیاتى کوردى لە شارى هەولێردا (1890 – 1958) - حەداد, عەبدوڵڵا محەمەد (Sulaimani Journal for Humanities, 2003)
This study deals with an important subject in the field of the history of Kurdish Literature in a city known of its an cientness, namely the city of Arbil, during the period between (1890 -1950) and as the subject is ramified, the researcher has preferred to divide it into several parts. What we publish here consists part one of the general study. It sheds light on the life and works of the pioneers of Kurdish Literature in the city of Arbil, those born before 1900. This part contains an introduction with a prelude and six chapters. In the first half of the prelude, the researcher puts forward a general view about the cultural and literary circumstances in Arbil during the 19th and early 20th c. while in the second half, he speaks about the poets of Arbil who were influenced by Kurdish Literature which appeared in the from of southern Kurdish dialect of the Kurdish Language in the 1 th c. In the six chapters devoted to the life and works of six literary figures, the researcher tries to present accurate information about the life of each one referring to the resources of their culture, through depending on the most trustful printed and manuscript references and resources. The researcher tries also to identify the literary and his torical values of the poets' works. After montioning the characteristies of their works in great accuracy the researcher reached a number of conclusions the first of which is that writing in Kurdish in Arbil emerged in the second half of the 19th c. Thus, the study unveils some unknown aspects of the subject. The next parts of the study will be devoted to the other stages of the subject which it is hoped to be tackled in the figure, zif God wishes. It remains to say, this study, in addition to concerning itself with necessary analyses; it attaches special importance to recording very important documental and historical information.